THE RELATIONSHIP OF BODY MASS INDEX (BMI) LEVEL AND SEVERITY OF PULMONARY TUBERCULOSIS IN PATIENTS AGED 18-64 YEARS AT GOTONG ROYONG HOSPITAL SURABAYA - Gunawan, Jovanka; Wahyuni Widoretno, Elisabeth Tri; Susan, Susan (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2024)
Background: Tuberculosis (TB) infection remains a concern for developing countries especially Indonesia due to its high prevalence and mortality rate. Malnutrition is often observed in TB patients. Malnutrition can be assessed through the Body Mass Index (BMI) level. Low BMI levels can increase the progression of pulmonary TB and resulting more severe manifestations in chest X-ray. The severity of pulmonary TB is determined based on the assessment of chest X-ray lesions, which categorized as mild, moderate, and severe.Objective: The aim of this study is to analyze the relationship between BMI levels and the severity of pulmonary TB in patients aged 18-64 years at Gotong Royong Hospital, Surabaya.Method: The method of this research is observational analytical with a cross-sectional design on pulmonary TB patients who underwent chest X-ray examinations before treatment. The study utilizes secondary data from the patient’s medical records, including weight, height, and chest X-ray images. Additional supporting data which is not available in the medical records were obtained through the patient responses using Google Form. Samples were taken according to the inclusion criteria and all data were collected at Gotong Royong Hospital from July to September 2023.Results: There are 39 samples collected in this research, consisted of 17 men and 22 women. The result based on Spearman correlation analysis revealed that the correlation between BMI levels and the severity of pulmonary TB has a p-value=0,397 (p > 0,05).Conclusion: There is no significant relationship between BMI levels and the severity of pulmonary TB in patients aged 18-64 years at Gotong Royong Hospital Surabaya.